Diagnostic Efficiency of the Child and Adolescent Symptom Inventory (CASI-4R) Depression Subscale for Identifying Youth Mood Disorders. Issue 5 (3rd September 2018) - Salcedo, Stephanie; Chen, Yen-Ling; Youngstrom, Eric A.; Fristad, Mary A.; Gadow, Kenneth D.; Horwitz, Sarah M.; Frazier, Thomas W.; Arnold, L. Eugene; Phillips, Mary L.; Birmaher, Boris; Kowatch, Robert A.; Findling, Robert L.
Abstract : This study examined the diagnostic and clinical utility of the Child and Adolescent Symptom Inventory–4 R (CASI-4 R) Depressive and Dysthymia subscale for detecting mood disorders in youth (ages 6–12; M = 9.37) visiting outpatient mental health clinics. Secondary analyses ( N = 700) utilized baseline data from the Longitudinal Assessment of Manic Symptoms study. Semistructured interviews with youth participants and their parents/caregivers determined psychiatric diagnoses. Caregivers and teachers completed the CASI-4 R. CASI-4 R depressive symptom severity and symptom count scores each predicted mood disorder diagnoses. Both caregiver scores (symptom severity and symptom count) of the CASI-4 R subscale significantly identified youth mood disorders (areas under the curve [AUCs] = .78–.79, p s < .001). The symptom severity version showed a small but significant advantage. Teacher symptom severity report did not significantly predict mood disorder diagnosis (AUC = .56, p > .05), whereas the teacher symptom count report corresponded to a small effect size (AUC = .61, p < .05). The CASI-4 R Depression scale showed strong incrememental validity even controlling for the other CASI-4 R scales. Caregiver subscale cutoff scores were calculated to assist in ruling in (diagnostic likelihood ratio [DLR] = 3.73) or ruling out (DLR = 0.18) presence of a mood disorder. The CASI-4 R Depressive subscale caregiver report can help identify youth mood disorders, and using DLRs may help improve diagnostic accuracy.